Application of Philosophy Values of Bhinci-Bhinciki Kuli in Early Childhood at Wolio Community - La Jeti Jeti; Manan Manan; Kadar Risman; Edison Edison (LPPM Universitas Pahlawan Tuanku Tambusai, 2021)
This research aimed to describe the application the philosophy values of Bhinci-bhinciki Kuli in early childhood at Wolio community. This research used descriptive method with ethnographic approach. The subjects of this research consisted of the chiefs . This research was conducted at wolio community In Buton. Method of data collection used observation and interviews. Based on the results of data analysis, showed that: The values of Bhinci-bhinciki Kuli included Poma-masiaka which means mutual love, Poangka-kataka which means mutual respect, Pomae-maeaka which means mutual respect for dignity and Popia-piara which means caring for one another. The Family had a very important role in instilling the values of philosophy Bhinci-bhinciki Kuli as a foundation of character through habituation and modelling since early childhood in daily life were accustomed and modelling Poma-masiaka mutual love, Poangka-kataka which means mutual respect, Pomae-maeaka which means mutual respect for dignity and Popia-piara which means caring for one another. Application the philosophy values of Bhinci-bhinciki Kuli in early childhood was to instill the values morality, so that grow up with a personality that had good character.